Capitalist agriculture between countryside and the city A study of two cases in Argentinean Pampas region - Bober, Gabriel Ivan (2013)
This article analyzes transformations in agriculture, agrarian structure and population dynamics in the context of economic expansion in Argentinean Pampas in recent decades. Increase of crops values, new technology packages available and local dynamics generate changes and new relationships between rural and urban areas. The study is a comparison of two different cases: one, is an example of processes of soybean production at Pampas region and the other exposes diversified dynamics of agriculture and urban expansion.